Down-modulation of heat shock protein 70 and up-modulation of Caspase-3 during schisandrin B-induced apoptosis in human hepatoma SMMC-7721 cells - Wu, Yi-Feng (World J Gastroenterol, 2004)
AIM: To investigate the effect of schisandrin B (Sch B) on proliferation and apoptosis of human hepatoma SMMC-7721 cells in vitro and regulation of Hsp70 and Caspases-3, 7, 9 expression by Sch B. METHODS: Human hepatoma cell line SMMC-7721 was cultured and treated with Sch B at various concentrations. Growth suppression was detected with MTT colorimetric assay. Cell apoptosis was confirmed by DNA ladder detection and flow cytometric analysis. The expression of Hsp70, Caspases-3, 7, 9 were analyzed by Western blot analysis. RESULTS: Sch B inhibited the growth of hepatoma SMMC-7721 cells in a dose-dependent manner, leading to a 50% decrease in cell number (LC50) value of 23.50 mg/L. Treatment with Sch B resulted in degradation of chromosomal DNA into small internucleosomal fragments, evidenced by the formation of a 180-200 bp DNA ladder on agarose gels. FCM analysis showed the peak areas of subdiploid at the increased concentration of Sch B. The results of Western bolt analysis showed that Hsp70 was down-regulated and Caspase-3 was up-regulated, while the activity of Caspases-7, -9 had no significant change. CONCLUSION: Sch B is able to inhibit the proliferation of human hepatoma SMMC-7721 cells and induce apoptosis, which goes through Caspase-3-dependent and Caspase-9-independent pathway accompanied with the down-regulation of Hsp70 protein expression at an early event.